Modular synthesis of dihydroxyacetone monoalkyl ethers and isosteric 1-hydroxy-2-alkanones - Gueclue, Deniz; Rale, Madhura; Fessner, Wolf-Dieter (European Journal of Organic Chemistry, 2015)
Straightforward methods for the efficient, systematic preparation of libraries of the title compound classes have been evaluated. A general and efficient modular route to dihydroxyacetone monoethers was developed based on trityl glycidol, which, through epoxide opening, oxidation, and deprotection, provided variously alkylated ethers by three routine operations in good overall yields (eight examples, 24-59%). The preparation of structurally related 1-hydroxyalkanones depends on the availability of the most economic starting materials and on their physicochemical properties. Thus, the most practical one-step approaches consisted of the sec-selective oxidation of short-chain 1,2-diols (<= C-6) using NaOCl, and the direct ketohydroxylation of 1-alkenes (>= C-6) using buffered stoichiometric KMnO4 or catalytic RuO4 with reoxidation by oxone, for which mostly good overall yields were achieved on a multigram scale (nine examples, 15-78%).
Keywords: Alkylation; Hydroxylation; Ketones; Oxidation; Oxygenation; Regioselectivity; synthetic methods

Advances in transition-metal-catalyzed C-H bond oxygenation of amides - Vijaykumar, Muniyappa; Punji, Benudhar (Synthesis-Stuttgart, 2021)
C-O bond formation represents a fundamental chemical transformation in organic synthesis to develop valuably oxygenated (hetero)arenes. Particularly, the direct and regioselective C-H bond oxygenation of privileged amides, using a transition metal catalyst and a mild oxygenating source, is a step-economy and attractive approach. During the last decade, considerable progress has been realized in the direct C-H oxygenation of primary, secondary, and tertiary amides. This Short Review compiles the advances in transition-metal-catalyzed oxygenation of C(sp(2))-H and C(sp(3))-H bonds on various amides with diverse oxygenation sources. The review is categorized into two different major sections: (i) C(sp(2))-H oxygenation and (ii) C(sp(3))-H oxygenation. Each section is discussed based on the directing group (monodentate and bidentate) attached to the amide derivatives.
Keywords: Amides; C-H activation; directing group; Oxygenation; Transition Metal